INTEGRASI PELAYANAN KEBIDANAN BERBASIS KOMUNITAS DALAM SISTEM KESEHATAN PRIMER - Yeni Trisna Purba; Arthauly Gracia Sinaga; Putri Handayani Simbolon (Politeknik Ganesha Medan, 2022)
Community-Based Midwifery Care (CMBC) is a crucial approach to improving the accessibility and quality of maternal and neonatal care, particularly in rural and remote areas. Integrating CMBC into primary health care (PHC) systems offers significant potential to strengthen overall health services, reduce disparities in access, and ultimately reduce maternal mortality (MMR) and neonatal mortality (NMR). This literature review examines the definition and principles of CMBC, successful integration models, and the benefits and challenges of integrating CMBC into PHC. The aim is to provide insights for policymakers, health program managers, and practitioners on how to strengthen the role of community midwives and maximize their contribution to achieving global health goals.